Functional Properties and Sensory Quality of Kombucha Analogs Based on Herbal Infusions - Marta Czarnowska-Kujawska; Joanna Klepacka; Małgorzata Starowicz; Patrycja Lesińska (MDPI AG, 2024)
Traditionally, kombucha is produced by the fermentation of black or green tea infusions with the use of SCOBY (Symbiotic Culture of Bacteria and Yeasts). However, SCOBY exhibits the ability to ferment other substrates as well, which can be used to create novel products with new sensory and health-promoting properties. This paper investigates the antioxidant activity, chemical composition, and sensory properties of mint, nettle, and blackcurrant leaf-based kombucha analogs. It has been demonstrated that the fermentation process with SCOBY significantly influenced (p ≤ 0.05) sugar, organic acids, and mineral contents, with the increase in iron, magnesium, and calcium amounts in all tested herbal kombucha. The study shows that the type of herb infusion has a significant influence on the parameters associated with antioxidant potential. The fermentation with SCOBY resulted in an increase in antioxidant activity as measured by the superoxide anion radical (O2•−) inhibition of all three tested herbal infusions, with the greatest changes observed in nettle kombucha. Herbal kombucha was characterized by significantly increased total phenolic content as determined by Folin's reagent and a changed phenolic compound profile by LC-MS/MS (liquid chromatography with tandem mass spectrometry) in comparison to nonfermented infusions. Very high sensory scores were achieved for fermented mint and blackcurrant-based kombucha.